Tirukkuṟaḷ uraivaḷam, Aṟattuppāl - Taṇṭapāṇi Tēcikar, Ca., 1906- (SAMP early 20th-century Indian books project, 1950)
Compilation of commentaries on Aṟattuppāl, part of Tirukkuṟaḷ, ancient Tamil didactic verse work, by Tiruvaḷḷuvar.